Natural constants as properties of the Spacetime structure. A geometrical and mathematical design - Gómez, Jose (2023)
In current physics there are two Natural constants with meanings that remain unresolved: the Cosmological and the Fine Structure constants. Both are related to the theory of relativity and quantum mechanics. Here we attempt to give meaning to each of these constants and the relationship that can exist between them by proposing a new system of units based on Spacetime Structure. We will extend this new concept to unsolved questions in physics and cosmology, as well as describing the process by which the Spacetime Structure premises were developed to provide a basis for our thesis that Spacetime is quantized in energy-linked equidistant vertices separating the Compton electron wavelength and time. Spacetime is an omni-tensional structure that contains the energy and mass composing the Universe. Within this structure atoms and photons undergo quantized movement from vertex to vertex, where the angle change between structural vertices produces the Spacetime curvature. We propose that the Fine Structure constant (α) is related to Spacetime Structure, and that physical properties of matter and energy can be translated to Structural or Spacetime Units, where Natural constants are described by mathematical relationships between the three pure numbers π, φ and α.